2016
DOI: 10.1590/s1806-92902016001000003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ensiling density on nutritive value of maize and sorghum silages

Abstract: -Studies were conducted to determine the effects of different ensiling densities on fermentation, aerobic stability, and nutritive value of maize and sorghum silages. Maize and sorghum were harvested at dough (363 g/kg) and milk stages (275 g/kg), respectively. Herbages were chopped approximately 1.5 cm after harvest and then ensiled in mini silos at high and low-bulk densities for 8.5 weeks. Different bulk densities were achieved by ensiling different weights of herbage in the fixed-volume mini silos (1.5-L a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
4
19
1
3
Order By: Relevance
“…Potentially, a difference in silage density is an important distinction between bales and can affect silage fermentation profile, dry matter loss and microbial activity (Sucu et al, 2016). In our experiment, initial bale characteristics, such as mean bale diameter, height, volume, weight and density were 1.28 and 1.24 m, 1.59 m 3 , 877 kg and 170 kg m 3 DM, respectively.…”
Section: Chemical Composition Fermentation Pattern and Microbial Promentioning
confidence: 65%
“…Potentially, a difference in silage density is an important distinction between bales and can affect silage fermentation profile, dry matter loss and microbial activity (Sucu et al, 2016). In our experiment, initial bale characteristics, such as mean bale diameter, height, volume, weight and density were 1.28 and 1.24 m, 1.59 m 3 , 877 kg and 170 kg m 3 DM, respectively.…”
Section: Chemical Composition Fermentation Pattern and Microbial Promentioning
confidence: 65%
“…In this way, the amount of air that penetrates the silo is minimized and undesirable aerobic micro‐organisms that lead to deterioration and quality losses during storage and feed‐out are inhibited (Johnson et al., ). In a study of Sucu, Kalkan, Canbolat, and Filya (), increased packing density resulted in silages with lower acetate, ammonia‐N and fermentation losses. Tightly packed silages remained stable upon exposure to air, showed increased nutrient digestibility and had higher energy contents than loosely packed silages.…”
Section: Introductionmentioning
confidence: 99%
“…The pH and the ammonia nitrogen are parameters that help to define a good silage fermentation, because are related to the acceptability of silage by the animals (Pahlow et al, 2003). Sucu et al (2016) in a study with sorghum silage with two densities (132 and 178 kg · m −3 of DM) after 60 days of ensiling observed that the silage with higher density showed higher WSC and CP contents and, consequently, lower DM losses (although no difference observed in the pH level). The pH values from 3.8 to 4.2 are expected in a well-preserved silage.…”
Section: Discussionmentioning
confidence: 97%
“…The proper density provide an anaerobic environment that is conducive to the LAB development resulting in increased lactic acid production and, consequently, lower pH (Pahlow et al, 2003;Sucu et al, 2016). The pH and the ammonia nitrogen are parameters that help to define a good silage fermentation, because are related to the acceptability of silage by the animals (Pahlow et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation